PENGARUH ETIKA BISNIS DAN STRATEGI MANAJEMEN BISNIS RITEL MODERN TERHADAP KINERJA RITEL TRADISONAL DI WATAMPONE - Kasmia Kasmia; Andi Sarjan; Aksi Hamzah (Institut Agama Islam Negeri (IAIN) Bone, 2021)
Abstrak This study discusses the influence of business ethics and modern retail business strategies on the performance of traditional retail in Watampone. This study aims to determine (1) the influence of modern retail business ethics on the performance of traditional retailers in Watampone, (2) the influence of modern retail management strategies on the performance of traditional retailers in Watampone, (3) how the simultaneous influence of business ethics and modern retail business management strategies on traditional retail at watampone.Based on the research objectives above, the type of research used is quantitative research with an Islamic economic approach and a sociological approach that is supported by observation methods, questionnaires and documents in collecting the required data. The collected data was then processed using multiple regression analysis. This is to determine the effect of business ethics and modern retail business management strategies on traditional retail in Watampone.The results of multiple regression analysis on the t test, a significant value of 0.000 0.05 and t count t table, namely 4.189 2.011, indicating that the business ethics variable (X1) has a significant effect on the performance variable (Y). Then H1 is accepted that there is an influence on the business ethics variable (XI) on the performance variable (Y). The results of multiple regression analysis on the t test, a significant value of 0.000 0.05 and t count t table (4.534 2.011) shows that the management strategy variable (X2) has a significant effect on the performance variable (Y). Then H1 is accepted that there is an influence on the management strategy variable (X2) on the performance variable (Y). The results of multiple regression analysis on the F test show an R value of 0.608 and an R Square value of 0.369, meaning that the simultaneous influence of business ethics (X1) and management strategy (X2) variables on performance variables (Y) is 36.9 percent. influence on the variables studied while the rest is influenced by other variables. So that the variables of business ethics (X1) and management strategy (X2) simultaneously influence the performance variable (Y).